Analisis Kinerja Pustakawan dalam Memberikan Jasa Layanan Informasi di Perpustakaan UIN Mahmud Yunus Batusangkar - Sri Wahyuni; T. Mulkan Safri (Pustabiblia: Journal of Library and Information Science, 2022)
Librarians have a role as an element of driving and organizing library services. Librarian's performance is a determining factor for the continuity of library life. Whether the library is good or not is closely related to how the services are provided to users. Therefore, the authors are going to analyze the extent to the performance of librarians. Providing services to users is described from the aspect of knowledge and abilities of librarians. The results showed that the librarian's performance was good and the user gave a positive impression in the attitude of the librarian, to provide service in a polite and friendly manner, showing the concern of a responsive and attitude in directing to the collection. It shows that the librarian worked professionally and responsibly. As a recommendation, the library is able to increase the number of library officers in order to maximize performance, especially in user services.